Dual-mode electrochemiluminescence and electrochemical sensor for alpha-fetoprotein detection in human serum based on vertically ordered mesoporous silica films - Chen, Haiyun; Huang, Jie; Zhang, Rongjing; Yan, Fei (Frontiers in Chemistry, 2022)
In this study, we demonstrated the highly sensitive detection of alpha-fetoprotein (AFP) by electrochemiluminescence (ECL) and electrochemistry (EC) based on the gated transport of the bifunctional probe (tris(1,10-phenanthroline) ruthenium (II) chloride, Ru (phen)3Cl2) into the nanochannels of vertically ordered mesoporous silica films (VMSFs). Due to the negatively charged surface and ultrasmall pore size, VMSF displays a signal amplification effect on Ru (phen)3Cl2 and is suitable for the construction of sensors with excellent sensitivity. With the linkage of (3-glycidyloxypropyl) trimethoxysilane, the anti-AFP antibody could covalently bind to the external surface of VMSF, generating a highly specific recognized sensing interface toward AFP. When AFP is presented, the formed immunocomplex hinders the diffusion of Ru (phen)3Cl2 to the underlying electrode surface, resulting in a decreased ECL or EC response. The dual-mode detection of AFP is achieved with a relatively low limit of detection (0.56 fg/ml for ECL and 4.5 pg/ml for EC) and a wide linear range (10 fg/ml∼1 μg/ml for ECL and 10 pg/ml∼1 μg/ml for EC). Moreover, owing to the inherent anti-fouling property of VMSF, satisfactory results in the analysis of human serum were obtained, showing the great potential of the designed strategy in clinical diagnosis.